Spatial and Temporal Trends of Recent Dissolved Phosphorus Concentrations in Lake Tana and its Four Main Tributaries. (11th May 2017) - Alemu, Muluken L.; Geset, Muhabe; Mosa, Hassan M.; Zemale, Fasikaw A.; Moges, Mamaru A.; Giri, Shree K.; Tillahun, Seifu A.; Melesse, Assefa M.; Ayana, Essayas K.; Steenhuis, Tammo S.
Abstract: Rapid population growth and agricultural intensification have been directly associated with land degradation and with visible deterioration in water quality in the Ethiopian lakes. Assessing the extent and origin of pollution is cumbersome because of the lack of measurements for water quality parameters. This paper reports on the dissolved phosphorus (DP) concentrations in Lake Tana and its tributaries during 3 years from 2010 to 2012 and the four rainy months in 2014. Concentrations in the headwaters, at the gaging station, at the river mouth, near shore (littoral), and in the open lake (pelagic) were measured for the four major rivers. DP concentration in the rivers was on the average 0·32 mg l −1, and DP in the lake was much lower with an average concentration of 0·10 mg l −1 . Temporally, DP concentrations were greater in the rainy phase of the monsoon than in the dry phase from November through March. Moreover, an upward trend in DP concentrations is coinciding with the area expansion of water hyacinths in the lake. Copyright © 2017 John Wiley & Sons, Ltd.